The Impact of Corporate Governance and Capital Struc-ture on Profitability of Infrastructure Sector Companies Listed in Indonesia Stock Exchange - Jesica Santoso; Mariana Ing Malelak (Politeknik Negeri Bengkalis, 2023)
This research is aim to discover the impact of corporate governance and capital structure on profitability. Corporate governance consists of board size, ownership concentration and board’s financial expertise, while capital structure consist of debt to assets ratio (DAR). With these variables, observation was made on infrastructure companies listed on Indonesia Stock Exchange. A purposive sampling was carried out on 11 companies within a research period of 2014-2021, which amounts to 88 observations. The results of the research using panel data regression show that ownership concentration, board’s financial expertise and debt to assets ratio have a significant impact on profitability. On the other hand, board size does not have significant impact on profitability of infrastructure sector companies.